Sectoral Labor Mobility and Optimal Monetary Policy - Cantelmo, Alessandro (IMF Working Papers; Working Paper ;, 2017)
In an estimated two-sector New-Keynesian model with durable and nondurable goods, an inverse relationship between sectoral labor mobility and the optimal weight the central bank should attach to durables inflation arises. The combination of nominal wage stickiness and limited labor mobility leads to a nonzero optimal weight for durables inflation even if durables prices were fully flexible. These results survive alternative calibrations and interestrate rules and point toward a non-negligible role of sectoral labor mobility for the conduct of monetary policy.